2022
DOI: 10.7150/ijms.73077
|View full text |Cite
|
Sign up to set email alerts
|

[6]-Gingerol induces Caspase-Dependent Apoptosis in Bladder Cancer cells via MAPK and ROS Signaling

Abstract: The anti-cancer effects of [6]-gingerol ([6]-GIN), the main active polyphenol of ginger (Zingiber officinale), were investigated in the human bladder cancer cell line 5637. [6]-GIN inhibited cell proliferation, increased sub-G1 phase ratios, and depolarized mitochondrial membrane potential. [6]-GIN-induced cell death was associated with the downregulation of B-cell lymphoma 2 (BCL-2) and survivin and the upregulation of Bcl-2-associated X protein (Bax). [6]-GIN activated caspase-3 and caspase-9 and regulated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Apoptosis is a natural mechanism by which cells induce programmed cell death and is a consequence of ROS produced in damaged cells [52]. In our fibrosis model, BLM generated a significant increase in apoptotic cells, as assessed by caspase-3 expression.…”
Section: Discussionmentioning
confidence: 79%
“…Apoptosis is a natural mechanism by which cells induce programmed cell death and is a consequence of ROS produced in damaged cells [52]. In our fibrosis model, BLM generated a significant increase in apoptotic cells, as assessed by caspase-3 expression.…”
Section: Discussionmentioning
confidence: 79%
“…Various studies have shown that ginger exhibits anti-inflammatory characteristics in treating cancer. A previous study reported that 6-gingerol repressed cell proliferation, enhanced the sub-G1 phase ratio, and depolarised the mitochondrial membrane potential of a human bladder cell line [78]. This active compound triggered cell death by downregulating B-cell lymphoma 2 (BCL-2) and survivin and upregulating the Bcl-2 associated X protein (Bax).…”
Section: Effect Of Mo and Ginger On Cancermentioning
confidence: 93%
“…Apoptosis is one of the major mechanisms resulting in controlled cell death which can be controlled by cancer cells. Many tumor cells can avoid apoptosis, thus they can multiplicate infinitely [ 87 ]. Qi Li et al found that exosomal miR-375-3p suppressed bladder cancer growth through promoting apoptosis in BC cells [ 80 ].…”
Section: Introductionmentioning
confidence: 99%